2006
DOI: 10.1002/adma.200502772
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of b‐Oriented TS‐1 Films on Chitosan‐Modified α‐Al2O3 Substrates

Abstract: Zeolite films have attracted much attention from the scientific community because of their potential applications as selective membranes, chemical sensors, and microelectronic devices. [1][2][3] The performance of permeable films can be greatly improved by controlling the crystal orientation on the substrate surface. [4,5] Thus far, significant progress in directing the crystal orientation on the substrate surface has been made for LTA and UTD-1, especially for MFI-type zeolite films.[6]Wang and Yan reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 35 publications
1
56
0
1
Order By: Relevance
“…[1][2][3] With the development of synthesis strategies and post-thermal treatments, zeolite membranes have been successfully utilized in separation, [4] catalytic reaction, [5] and optoelectronic devices. [6] A defectfree zeolite membrane can principally distinguish components in gaseous and liquid mixtures due to its molecular sieving effect and the mutual interactions between the molecules and the zeolitic pores.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] With the development of synthesis strategies and post-thermal treatments, zeolite membranes have been successfully utilized in separation, [4] catalytic reaction, [5] and optoelectronic devices. [6] A defectfree zeolite membrane can principally distinguish components in gaseous and liquid mixtures due to its molecular sieving effect and the mutual interactions between the molecules and the zeolitic pores.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, containing abundant amino and hydroxy groups, was used as the orientation-directing matrix for the synthesis of boriented TS-1 films. [10] Glutaraldehyde-crosslinked chitosan (GA-CS) hydrogels were recently used to control zeolite crystallization, and thus zeolite A and Y nanocrystals were synthesized. [11] It is noted that chitosan is only soluble in an acidic aqueous solution, and the resulting chitosan solution turns into a polymer hydrogel when an alkaline solution penetrates through the gel.…”
mentioning
confidence: 99%
“…Recently, it was reported that continuous b -oriented MFI zeolite fi lms can be synthesized by microwaveassisted in situ crystallization and that a certain nuclei concentration at the aging stage is necessary [ 45 ]. b -Oriented TS-1 fi lms could be grown on chitosan-modifi ed α-Al 2 O 3 substrates [ 46 ].…”
Section: Oriented Mfi-type Zeolite Films and Membranesmentioning
confidence: 99%